Integrated synthesis of metallocene@support catalysts based on glyphosate and its zirconium derivatives. Issue 88 (8th December 2017) - Zhou, Annan; Zhang, Yuejuan; Shi, Yasai; Xu, Qinghong
Abstract : Three new kinds of composite metallocene catalyst, Cp2 Zr@Gly, Cp2 Zr@ZrGp and Cp2 Zr@EXZrGP, were synthesized and their catalytic activity in ethylene polymerization was studied. Abstract : Three new kinds of composite metallocene catalyst, Cp2 Zr@Gly, Cp2 Zr@ZrGp and Cp2 Zr@EXZrGP, for ethylene polymerization were synthesized based on matrixes of glyphosate (Gly), layered zirconium glyphosate (ZrGP) and exfoliated zirconium glyphosate (EXZrGP), and their catalytic activity in ethylene polymerization was studied. The catalytic activities of Cp2 Zr@Gly, Cp2 Zr@ZrGp and Cp2 Zr@EXZrGP are 3.8 × 10 5, 3.3 × 10 5 and 4.8 × 10 5 gPE per molZr per h per bar at a temperature of 60 °C and after a time of 1.0 h, higher than that of the catalyst Cp2 ZrCl2 @SiO2 (2.3 × 10 5 gPE per molZr per h per bar), which is now used in industry. The catalytic activities of the three new catalysts are also higher than that of the catalyst Cp2 ZrCl2 (3.0 × 10 5 gPE per molZr per h per bar) under the same conditions. Exfoliation of the activity centers from the support and reactor fouling phenomena were all found to be avoided during the course of the polymerization.